Power Generation and Storage Application Technologies (International Journal of Innovative Research in Engineering & Management, 2021)
In this article we evaluate the ecological impressions of  carbon capture and use (CCU) and carbon capture and storage  (CCS) of technologies. To this end research on the assessment  of the life cycle from the different literatures has been  addressed. There are a total of 27 reports, 11 on CCS and 16  on CCU. CCS research has shown that power plants will  reduce their global warming potential (GWP) from 63 to 82  percent, with combustion of oxygen fuel in pulverized coal  and integrated combined cycle gasification (IPCG) plants to  the greatest reduction and post-combustion capture in  combined-cycle gas turbine (CCGT) plants, achieving the  least reductions. CCS has higher environmental impacts than  without acidification and human toxicity. The GWP for CCU  varies greatly depending on how it is used. Mineral  carbonation will decrease GWP by 4% to 48% compared to  no CCU. In addition, compared to conventional DMC  techniques, under CO2 lowers the GWP by 4.3 times and  ozone depletion by 13 times for chemical extraction.
Keywords: Carbon Capture; Climate Change; Combustion; Storage; Sustainable Development